Europe must deliver at the level closest to the citizens Subsidiarity: Past, present and future. Issue 1 (April 2019) - Schneider, Michael
Subsidiarity is a core value of the European People's Party. It has been incorporated in the EU treaties to ensure that decisions are taken as closely as possible to the citizens. At a time when citizens are increasingly putting Europe's democratic legitimacy into question, it is essential to place this principle at the heart of discourse on the EU. The Task Force on Subsidiarity, Proportionality and Doing Less More Efficiently, which was set up by European Commission President Jean-Claude Juncker in November 2018, has identified a 'new way of working'. It gives local, regional and national authorities a stronger voice in EU policymaking, with the aim of improving the quality and effectiveness of legislation. If implemented by the different institutions, it will both ensure that EU legislation adds value and lead to the member states and their regions and cities taking greater ownership of EU decisions. And these developments, in turn, will help reconnect Europe with its citizens.